Comparison of Sodium Levels in Patients with Stage V Chronic Kidney Disease Whose Using New and Re-use Hemodialyzer in Hemodialysis Installation RSD dr. Soebandi Jember - Yuli Hermansyah; Firda Novidyawati; Ayu Munawaroh Azis (Faculty of Medicine, University of Jember, 2020)
Stage V Chronic Kidney Disease (CKD) is one of the most common medical case in the world. Stage V CKD defined as a condition where the renal function decrease progressively, marked by the GFR <15/ml/minute/1,73 m2, with or without kidney damage history for three months. Patients diagnosed with Stage V CKD often needs kidney replacement therapy, one of which is hemodialysis. The cost needed for hemodialysis was considered as too expensive, forcing lots of medical staff in most countries using the method known as re-use hemodialyzer. Re-use hemodialyzer is a term for using the same hemodialyzer (or hemodialysis machine) for the same patient but on a different therapy session. The main purpose for this research is to investigate the sodium level in patients with Stage V CKD whose using new and re-use hemodialyzer in Hemodialysis Installation of RSD dr. Soebandi Jember. Analytic Observational Study is used for this research combined with Cross Sectional Study in December 2018. Total of 19 samples chosen with inclusion and exclusion criteria. Collected data is analyzed using paired t-test. The conclusion that can be obtained from this research is that there is no significant difference between sodium level in patients with Stage V CKD whose using new and re-use hemodialyzer (p=0,904). The effectivity and quality of the hemodialyzer is thought to be the main factor for this result. Keywords: Chronic Kidney Disease, sodium, re-use hemodialyzer